Luke historian and theologian - Marshall, Ian Howard, 1934- (Channel Islands, UK Gurnsey, 1988)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Luke -- commentaries; Bible. N.T. Acts -- commentaries